Implementation of Good Environmental Governance in Indonesia: Literature Review - Pawara, Baso; Haslinda (Pemuda Peduli Publikasi Insan Ilmiah, 2026)
Purpose: This study aims to examine how Good Environmental Governance has been implemented in Indonesia by synthesizing existing academic literature across environmental sectors and governance levels. It seeks to identify dominant governance principles, recurring implementation patterns, and structural challenges, while linking sectoral findings to broader debates on governance quality and sustainable development. Subjects and Methods: The study employed a literature review design. Peer-reviewed journal articles, academic books, book chapters, and selected policy reports related to environmental governance in Indonesia were systematically collected from major academic databases. The reviewed literature primarily covers the post-decentralization period. Data were analyzed using a thematic synthesis approach guided by core Good Environmental Governance principles, including transparency, accountability, participation, rule of law, effectiveness, and equity, to ensure analytical coherence and theoretical rigor. Results: The findings indicate that Indonesia has formally incorporated Good Environmental Governance principles into its environmental policy framework. Transparency initiatives, participatory mechanisms, and collaborative governance arrangements have expanded across several sectors. However, the literature consistently reveals weak regulatory enforcement, limited institutional capacity, fragmented authority under decentralization, and persistent power asymmetries. As a result, environmental outcomes remain uneven, with localized governance successes coexisting alongside continued deforestation, pollution, and resource conflicts. Conclusions: The study concludes that the implementation of Good Environmental Governance in Indonesia remains partial and context-dependent rather than fully institutionalized. Strengthening environmental outcomes requires integrated improvements in accountability, institutional capacity, and political commitment. This review contributes to the literature by offering an integrative governance perspective and highlights the need for future research focusing on subnational variation, long-term governance dynamics, and political–economic drivers of environmental decision-making.